Rovearinids (stemless crinoids) in the Albian carbonates of the offshore Santos Basin, southeastern Brazil: stratigraphic, palaeobiogeographic and palaeoceanographic significance - Dias-Brito, D.; Ferre, B. (Elsevier B.V., 2001)
Microfacies analysis of marine carbonates cored by Petrobras well 1-SPS-6 in the offshore Santos Basin (southeastern Brazil) has revealed a remarkable fossil assemblage of calpionellids (colomiellids), favusellids, hedbergellids, globigerinelloidids, buliminids, radiolarians, inoceramid prisms, roveacrinids, and saccocomids(?) preserved in lower Albian calcimudstones-wackestones of the lower part of the Guaruja Formation. This assemblage represents an allochtonous accumulation in a deep neritic to shallow bathyal hypoxic environment. Besides 'saccocomid-like' sections, the only determinable sections of roveacrinids are thecal plates of Poecilocrinus dispandus elongatus Peck, 1943. This species was previously only known from the Weno Formation of Texas. The Brazilian material extends its records farther south from at least the lower Albian, which then represents the earliest occurrence of this peculiar family in the South Atlantic region. Taking into account their Albian global distribution and the location of their oldest representative (Hauterivian near Alicante, Spain), the Roveacrinidae dispersed westward throughout all of Cretaceous Tethys. The Tethyan origin of Roveacrinidae is further evidence that, during late Aptian-Albian times, the northern South Atlantic (north of the Walvis-SBo Paulo Ridge) was supplied by a Tethyan water mass. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: Cretaceous; Albian; Brazil; roveacrinds; carbonate rocks; Tethys